Navy SEALs - Hamilton, John, 1959- (Hamilton, John, 1959- Xtreme Armed Forces., 2021)
Explores the history of the U.S. Navy SEALs, covering the elite group's origins and functions, the training required for its members, the weapons and equipment SEALs use, and their different types of missions. Also discusses their importance to the future of the United States. Includes color photographs, a quiz, fact boxes, a glossary, and online resources.